Effect of Camellia nitidissima Chi Polysaccharide on the Physicochemical Properties and Gel Properties of Surimi Gel in Pangasius bocourti - Zezheng ZENG; Lifeng ZHU; Yanghong CAO; Cen QI; Ziru DAI; Qingliang DONG (Shipin gongye ke-ji)
In this work, Camellia nitidissima Chi polysaccharide (CNCP) was incorporated into Pangasius bocourti surimi, and then the CNCP-Pangasius bocourti surimi plural gel was fabricated via a two-stage heating approach to improve the quality of Pangasius bocourti surimi. The effects of different CNCP dosages (0%, 0.2%, 0.4%, 0.6%, 0.8%, 1.0%) on the whiteness value, gel strength, textural properties, sensory evaluation, cooking loss rate, water-holding capacity, water distribution, dynamic rheological characteristics, gel-forming forces, protein secondary structure, and microstructure of the CNCP-Pangasius bocourti surimi plural gel were also investigated. The results indicated that with the increase of CNCP dosage, the gel properties of prepared gels initially rose and then declined. The strongest gel strength was observed to be 202.59 g·cm for the CNCP-Pangasius bocourti surimi plural gel with 0.4% CNCP dosage. Also, the hardness, sensory score, and water-holding capacity were enhanced by 20.1%, 35.02%, and 23.2%, respectively, compared to the control group. Furthermore, it had the highest storage model (G'), the free water content was only 2.3%, the relaxation time of the constrained water was significantly shortened, the cooking loss rate was significantly reduced, the disulfide bond content was significantly increased (P<0.05), and the transformation of the α-helix to the more stable β-fold structure was achieved. At this time, the CNCP-Pangasius bocourti surimi plural gel had the densest structure with the smallest microstructural pores and the largest fractal dimension. In conclusion, the addition of CNCP could form a dense plural gel network with Pangasius bocourti surimi, thereby improving the quality of surimi gel. This work would provide a novel perspective for the further development of high-quality and healthy surimi products.